النقد الأدبي الإسلامي بين التّنظير والتّطبيق( قراءة في كتابات عماد الدّين خليل ) (El-Wahat Journal for Research and Studies, 2023)
ملخص:لقد برزت الفكرة الأدبية والنقدية المنبثقة عن التصور الإسلامي في العصر الحديث، وأخذت   تتطور على يد أدباء ونقاّد دعوا إلى تقديم مشروع بديل إسلامي، والوقوف في وجه المناهج الغربية  وكان من أبرزهم الناقد العراقي عماد الدين خليل، ويهدف هذا البحث إلى تقديم صورة واضحة عن الخطاب النقدي الإسلامي المعاصر، وكشف  التجربة النقدية للناقد من خلال قراءة في كتاباته في جانبها التنظيري، الذي تناول فيه التصور الإسلامي، والنقد الإسلامي، ومرجعيات الخطاب، والقضايا النقدية، والجانب التطبيقي الذي يبين الحقول الأدبية التي تضمنها النقد التطبيقي عنده، من خلال نقد الشعر والقصة والرواية والمسرح .كلمات دالة: النقد، المناهج، الغربي، الخطاب، عماد الدين خليل، القضايا النقدية.             Abstract:  The idea of literary criticism which has been emerged from the Islamic perception in modern era was developed by writers and critics who advocated an alternative Islamic project against Western approaches. One of the most prominent figures was the Iraqi critic Imad Eddine khalil. This research aims at giving clear image on critic of the contemporary Islamic discourse. Moreover، it shows critical experience among critics through reviewing his writings from theoretical perspective which deals with: Islamic perspective، Islamic criticism، discourse background and critical issues. Another practical part that explains literary fields which is included in practical criticism through the criticism of poetry، story، novel and theatre Key words: criticism, curricula, Western criticism, discourse, Imad al-Din Khalil, critical issues.